Social Media and Tourist Decisions: A Study on Kintamani, Bali as a Leading Destination - Putu Sri Darmayanti; I Made Trisna Semara; Pricilia (Journal of Business on Hospitality and Tourism, 2025)
This study aims to analyze the influence of social media exposure on tourists’ decisions to visit Kintamani as one of Bali’s leading destinations. Social media plays an important role in shaping tourists’ perceptions and interests through visual content, reviews, and user-shared information. Kintamani was chosen as the research location because of its main attractions: Mount Batur, Lake Batur, its cool highland climate, and its status as a strategic tourism area in Bali Province. The research employed a quantitative approach with a survey method targeting tourists visiting Kintamani. The sampling technique was accidental sampling, and the research instrument was a questionnaire with a five-point Likert scale. Data were analyzed using simple linear regression via SPSS version 25. The results showed that social media exposure has a positive and significant effect on tourist decisions. The regression equation obtained was Y = 22.698 + 0.417X, with a t-test value of 2.284 and a significance level of 0.025 (<0.05), proving the hypothesis of significant influence. The correlation coefficient (R) = 0.263 indicates a low-level relationship, while R Square = 0.069 suggests that social media exposure explains only 6.9% of the variance in tourist decisions, with the remaining 93.1% influenced by other factors. Simultaneously, the ANOVA test yielded an F-value of 5.217 with significance at 0.025 (<0.05), confirming that the regression model is significant overall. The findings highlight that although the contribution of social media exposure to tourist decisions is relatively low, it remains significant and influential in encouraging tourism visits to Kintamani. Therefore, digital marketing strategies through social media should continue to be optimized but also supported by other factors such as destination quality, facilities, tourist experiences, and personal recommendations to be more effective in attracting tourists.